Sosialisasi Legalitas Usaha Untuk Masa Depan UMKM Yang Berkelanjutan - Manzilah Ar Rohmah; Muhimmatur Rodhiyah; Farah Fadiyah; Rachmawati Fidia; Elfi Haniatul Mahfiroh; Safira Khoirotunnisa; Nafia Ilhama Qurratu’aini (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
This research explores the vital role of business legality in supporting the growth and sustainability of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Through a combination of interview and direct observation approaches, we investigate the challenges faced by MSMEs in obtaining appropriate business legality and its impact on market access and financing. The findings indicate that a lack of understanding of the importance of business legality, complex licensing processes, and the need for specific requirements are major obstacles for MSMEs, especially those operating at the micro and small levels. Furthermore, we conclude that complete and legally valid business legality forms a solid foundation for the growth of MSMEs, enabling broader access to formal markets and financial resources. The approach of mentoring in obtaining the Business Identification Number (NIB) emerges as an effective solution in assisting MSMEs in overcoming challenges related to business legality. Comprehensive mentoring programs, ranging from education about the registration process to practical assistance in gathering required documents, provide much-needed support for MSMEs like Bu Siti in navigating complex registration processes. Evaluation and feedback, as well as effective information dissemination, also prove crucial in increasing MSMEs' awareness and understanding of licensing procedures and the benefits of having complete business legality. Thus, collaborative efforts from various parties can help create a more conducive environment for the growth of MSMEs in Indonesia.